СМЕШАННАЯ ЗАДАЧА ДЛЯ УРАВНЕНИЯ ЧЕТВЕРТОГО ПОРЯДКА С СИНГУЛЯРНЫМ КОЭФФИЦИЕНТОМ В ПРЯМОУГОЛЬНИКЕ (Scientific journal of the Fergana State University, 2023)
In the present work with spectral method it was proved the uniqueness and existence of the solution of the mixed problem for a fourth order equation with singular coefficients in a rectangular domain.